Experimental and theoretical development of a tracer gas method for measuring trapping efficiency in internal combustion engines - Olsen, Daniel B., author; Willson, Bryan, advisor; Mitchell, Charles E., advisor; Dandy, D. S., committee member; Kirkpatrick, Allan, committee member (Colorado State University. Libraries, 1999)
An investigation into a tracer gas method for determining trapping efficiency in 4-stroke and 2-stroke cycle engines is described. Potential difficulties with the technique are identified and analyzed. These potential difficulties include incomplete cylinder tracer reaction, exhaust tracer instability, and inconsistent exhaust sampling. Tracer gas global chemical kinetic mechanisms are reviewed and used as a means for tracer gas selection. Multiple step chemical kinetic mechanisms are implemented to predict tracer destruction in the cylinder and tracer consumption in the exhaust. The tracer gases investigated are nitrous oxide (N20) and monomethylamine (CH3NH2). As a benchmark the oxygen tracer technique, where oxygen in the intake air is used as the tracer, is evaluated for application to 4-stroke cycle engines. Equations and procedures for performing tracer gas measurements and analysis are developed. Test results are presented for a GM 5.7 1, 8 cylinder, 4-stroke cycle, gasoline engine and a Cooper-Bessemer GMV-4TF 141 1, 4-cylinder, 2-stroke cycle, natural gas engine. Results include evaluation of tracer cylinder reaction efficiency, assessment of the extent of tracer exhaust reaction, and trapping efficiency measurements. Of the tracers considered, N20 is determined to be optimal for both applications. The tracer gas method is utilized to determine the engine speed at which maximum short-circuiting occurs in the 4-stroke cycle engine. Results of scavenging investigations using the tracer gas method are described for the 2-stroke cycle engine for various operating conditions. The scavenging investigations include evaluation of trapping efficiency, delivery ratio, scavenging efficiency, and trapped equivalence ratio. The engine operating condition variations investigated are changes in boost, speed, back pressure, and port restriction.
Keywords: mechanical engineering; automotive materials; chemical engineering; automotive engineering